Warisata: A Genealogy of Education from the Suma Qamaña - Viedma, María Celeste (2015)
This essay aims to establish a relation of continuity between the pedagogy supported by the leading exponents of the experience of the ayllu school Warisata and the current educational reform driven by the government of Evo Morales in Bolivia. Political positions by the identification of an enemy are analyzed, as well as the integration of pedagogical practice and its link with the community, territorial and practical aspects. It works mainly with books written by Elizardo Pérez Warisata. The Ayllu school and Carlos Mostajo The Taika. Theory and practice of ayllu school, on one hand, and the Law on Education